Influence of the auxiliary acceptor and π-bridge in triarylamine dyes on dye-sensitized solar cells. Issue 8 (15th July 2019) - Xie, Yan; Zhou, Hai; Zhang, Shaozheng; Ge, Chengsheng; Cheng, Shenyu
Abstract : Four new dyes based on triarylamine donors with different π-bridges have been synthesized and showed the best overall conversion efficiency η of 7.92% (that of N719 dye was 8.53% under the same conditions). Abstract : Four metal-free organic dyes (AFL7–AFL10 ) based on triarylamine donors and different π-bridges with or without a benzothiadiazole auxiliary acceptor have been synthesized. The dyes' photophysical and electrochemical properties, theoretical calculations, and dye-sensitized solar cell (DSSC) performances have been investigated. Electrochemical measurement data indicate that varying the π-conjugacy system can tune the HOMO and LUMO energy levels. A high molar extinction coefficient combined with a broad absorption spectrum helps to reinforce the dyes' light harvesting ability; therefore, it could help to increase the J SC of the DSSCs. Among the four dyes, AFL7 bearing the bithiophene bridge achieves the best photocurrent performance with a J SC value of 16.94 mA cm −2, corresponding to an overall conversion efficiency η of 7.92% under standard AM 1.5 G conditions (that of N719 dye was 8.53% under the same conditions). The results show that the dyes based on the triarylamine donor containing fluorenyl and biphenyl moieties are promising candidates for improving the performance of DSSCs.